Bilingualism and Cognition: An Annotated Bibliography on the Impact of Bilingualism on Brain Function and Cognitive Abilities - Azzawiyatul Annajiyah; Azlin Azlina; Ken Izzun Nadhifah; Luthfiyah Rahma Ahmadany; Masyitah Noviyanti; Azzawiyatul Annajiyah; Azlin Azlina; Ken Izzun Nadhifah; Luthfiyah Rahma Ahmadany; Masyitah Noviyant (INTENS (International Journal of English Education and Linguistics), 2026)
Bilingualism has received increasing attention in cognitive science and applied linguistics due to its potential influence on brain function and cognitive abilities across the lifespan. This study aims to examine how bilingualism is conceptualized and discussed in relation to cognition, executive control, and neural adaptation through a structured annotated bibliography. Employing a qualitative descriptive approach, this study reviews and critically evaluates ten selected scholarly sources, including journal articles, book chapters, and review studies, using document analysis to identify their objectives, theoretical frameworks, methods, key findings, and scholarly contributions. The results indicate that bilingualism is consistently portrayed as a cognitively demanding experience that engages executive control and attentional systems, leading to adaptive changes in cognitive and neural functioning rather than simple transfer effects. However, the reviewed literature also reveals considerable variability in cognitive outcomes, influenced by factors such as age of acquisition, language proficiency balance, and patterns of language use. In conclusion, this annotated bibliography demonstrates that the cognitive effects of bilingualism are complex, context-dependent, and shaped by individual bilingual experiences. The originality of this study lies in its systematic organization and critical evaluation of influential works on bilingualism and cognition, providing a coherent overview that clarifies ongoing debates and offers implications for future research in cognitive science, linguistics, and educational contexts.